Efficient removal of bovine serum albumin from water by cellulose acetate membranes modified with clay and titania nano particles - Refaat, Heba M.; Ashraf, Nada; El-Dissouky, Ali; Tieama, Hossam A.; Kamoun, Elbadawy A.; Showman, M. S. (Frontiers in Chemistry, 2023)
Modified cellulose acetate membranes with bentonite clay (CA/bent) and TiO2 nanoparticles (CA/TiO2) using the phase inversion method are prepared and characterized. These Membranes are favored due to their high salt rejection properties and recyclability. The IR and EDX spectral data indicate the formation of modified membranes. The SEM micrographs show that the modified membranes have smaller particle sizes with higher porosity than the neat membrane. The average pore diameter is 0.31 µm for neat cellulose acetate membrane (CA) and decreases to 0.1 µm for CA/0.05bent. All modified membranes exhibit tensile strengths and elongation percentages more than the neat membrane. The higher tensile strength and the maximum elongation% are 15.3 N/cm2 and 11.78%, respectively, for CA/0.05bent. The thermogravimetric analysis of modified membranes shows higher thermal stability than the neat membrane. The modified membranes exhibit enhanced wettability and hydrophilicity compared with CA, by measuring the contact angle which decreases from 60° (CA) to 40° (CA/0.1bent). The ultrafiltration tests indicated that the CA/bent and CA/TiO2 are better than CA. The most efficient nanocomposite membrane is CA/0.05bent with 100% removal of (BSA) from industrial water with a flux equal to 9.5 mL/min under an applied pressure of 20 bar. Thus, this study introduces a novel ultrafiltration membrane (CA/0.05bent) that can be used effectively to completely remove BSA from contaminated water.